Analysis of Middle School Mathematics Applications Textbook Activities Based on Model-Eliciting Principles - Dündar, Rüveyda Karaman; Bora, Rabia Betül; Dündar, Rüveyda Karaman (My University, 2024)
Model-eliciting activities (MEA) represent a distinct form of problem-solving exercises that deviate from conventional problem-solving approaches. They encompass complex real-life scenarios characterized by multiple feasible solutions, demanding non-routine thinking with open-ended possibilities. Lesh and Doerr (2003) posit that MEA conform to specific principles, encompassing model construction, reality, self-evaluation, model externalization (construct certification), model generalization, and effective prototype principles. This study examines the compatibility of tasks in Turkey's middle school mathematics applications textbooks (grades 5-8) with the principles of model-eliciting activities (MEA). The analysis focuses on five principles: reality, model construction, self-evaluation, model documentation, and model generalization. The findings reveal varying degrees of compatibility across different grades. The reality and model generalization principles show more robust compatibility, while the model construction and model documentation principles have mixed levels of compatibility. The self-evaluation principle demonstrates varied compatibility. The study highlights strengths and areas for improvement in the tasks' alignment with MEA principles and emphasizes the importance of real-life relevance and model application. Suggestions are made to enhance explicit guidance in model construction and documentation. The study provides implications for curriculum design, teacher professional development, instructional strategies, student engagement, assessment practices, and future research in mathematics education. However, limitations, such as the absence of student perspectives and contextual factors, should be considered when interpreting the findings.
Keywords: Eğitim; Eğitim Araştırmaları; Textbook; Mathematical modeling; Middle school; Model-eliciting activities; Modelling principles